Immunosuppressive regimens on conversion of cytomegalovirus infection to disease in liver transplant recipients - Amirhassan Rabbani; Shiva Aliabbar; Saman Nikeghbalian; Seyed Ali Malek-hosseini; Mana Baziboroun (Babol University of Medical Sciences, 2022)
Background: Cytomegalovirus (CMV) disease is one of the most common infectious complications after liver transplantation. It is the cause of numerous morbidity and mortalities. Intensity of immunosuppression defined as overall immunosuppressive drug dosage seems to affect infectious complications. The main purpose of this study is to investigate the intensity of immunosuppression on conversion of CMV infection to disease in this population. Methods: In this cross-sectional study, we retrospectively evaluated and analyzed the data of all recipients who underwent orthotopic liver transplantation (OLT) between March 2014 and March 2016 and had positive serum PCR for CMV after transplantation in follow- up course. Of 134 recipients, only 66 adult liver transplant recipients were eligible to be studied.  Multiple variables such as MELD score, cold ischemic time, warm ischemic time, operative data, immunosuppressive drugs and regimen, plasma CMV viral load, donor and recipient CMV IgG serostatus were recorded and analyzed. Results: of the 66 patients, 50 (76%) had CMV infection and 16 (24%) had disease. There was significant association between donor CMV IgG serostatus, extra corticosteroid pulse therapy, acute cellular rejection, serum tacrolimus level and conversion of CMV infection to CMV disease (P=0.005, 0.001, 0.031, 0.031). Conclusion: It seems that the intensity of immunosuppression has influence on conversion rate of CMV infection to disease in liver recipients.